Separation and purification of L‐proline and L‐hydroxyproline from the hydrolysate of sea cucumber Acaudina leucoprota. Issue 12 (10th July 2018) - Zhou, Haiyan; Zhang, Yali; Xue, Yaping; Lin, Saijun; Zheng, Yuguo
Abstract: BACKGROUND: Sea cucumber Acaudina leucoprocta is a low‐value marine product with high contents of heavy metals in the body wall. However, it could be used as a substitute source of land‐based animals for value‐added products L‐proline (L‐Pro) and L‐hydroxyproline (L‐Hyp). For high recoveries and purities of L‐Pro and L‐Hyp from A. leucoprocta hydrolysate, the preparative separation of these imino acids with cation exchange resins was investigated. RESULTS: Among 11 cation exchange resins tested, Dowex 50WX8 resin offered the best separation capacity for L‐Pro and L‐Hyp from each other and impurities. The static equilibrium adsorption data fitted well with the Langmuir isotherm, and the adsorption kinetic followed the pseudo‐second‐order model. For the most effective ion exchange process, the adsorption and desorption parameters of L‐Pro and L‐Hyp were optimized with the column packed with Dowex 50WX8 resin. Under optimal conditions, the preparative separation of L‐Pro and L‐Hyp was easily and effectively achieved. The L‐Pro purity increased from 55.7% in the extract of A. leucoprocta hydrolysate to 94.3% in the eluent, and the L‐Hyp purity increased from 27.8% to 95.7%; their final recovery yields from the extract of A. leucoprocta hydrolysate were 93.3% and 89.4%, respectively. CONCLUSION: Our study provided an effective approach for large‐scale production of imino acids extracted from low‐value sea products, and offered a scientific reference for the separation of other valuable components. © 2018 Society of Chemical Industry